2022
DOI: 10.1186/s12957-022-02620-3
|View full text |Cite
|
Sign up to set email alerts
|

UCHL1 acts as a potential oncogene and affects sensitivity of common anti-tumor drugs in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma is the leading cause of cancer death worldwide. Recently, ubiquitin C-terminal hydrolase L1 (UCHL1) has been demonstrated to be highly expressed in many tumors and plays the role of an oncogene. However, the functional mechanism of UCHL1 is unclear in lung adenocarcinoma progression. Methods We analyzed the differential expression of the UCHL1 gene in lung adenocarcinoma and normal lung tissues, and the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…UCHL1 plays a vital role in anti-apoptosis, cancer cell invasion, migration and proliferation. Moreover, it enhances the multi-drug resistance in different cancer cells and tissues [ 73 , 74 , 75 ]. A previous study showed that UCHL1 overexpression supported apoptosis in verapamil- and Adriamycin-treated hepatoma cell lines (BEL-7402 and SMMC-7721) [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UCHL1 plays a vital role in anti-apoptosis, cancer cell invasion, migration and proliferation. Moreover, it enhances the multi-drug resistance in different cancer cells and tissues [ 73 , 74 , 75 ]. A previous study showed that UCHL1 overexpression supported apoptosis in verapamil- and Adriamycin-treated hepatoma cell lines (BEL-7402 and SMMC-7721) [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of UCHL1 by siRNA attenuated the cell apoptosis effect of combined drugs, which indicated the important role of UCHL1 in the verapamil-mediated reversal of drug resistance [ 76 ]. In another study, UCHL1 overexpression improves the early diagnosis and detection rate and provides targeted drug therapy for lung adenocarcinoma [ 75 ]. The underlying mechanism of UCHL1 mediated MDR to P-glycoprotein (P-gp) substrate drugs and the increased invasion and migration in resistant breast cancer cells compared to the sensitive phenotype, which might be associated with MAPK/Erk pathway activation [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…162 In lung adenocarcinoma, UCHL1 promotes tumor metastasis, inhibits apoptosis, and is significantly involved in patient prognosis. 163 In line with these findings, the knockdown of UCHL1 was recently reported to limit the proliferation and migration of HN6 HNSCC cells. 158 Nevertheless, there are contradicting data demonstrating that exogenous expression of UCHL1 inhibited the proliferation of LNCaP prostate cancer cells via p53-induced Akt inhibition as well as p27 accumulation.…”
Section: Deubiquitinasesmentioning
confidence: 60%
“…Further, silencing UCHL1‐mediated reduction of uterine serous carcinoma cell proliferation is carried out through attenuating cyclin‐B1 expression as well as cell cycle progression 162 . In lung adenocarcinoma, UCHL1 promotes tumor metastasis, inhibits apoptosis, and is significantly involved in patient prognosis 163 . In line with these findings, the knockdown of UCHL1 was recently reported to limit the proliferation and migration of HN6 HNSCC cells 158 .…”
Section: The Role Of Ups Dysregulation In Tumorigenesismentioning
confidence: 91%
“…GABRP, BCL11A, and UCHL1 have been reported as key-coding RNAs that play important roles in inducing resistance of carcinoma cells to chemoendocrine therapy and/or radiotherapy. [27][28][29] In addition, since GABRP, MMP7, and CYP4F3 are known to participate significantly in the tumor immunity of carcinomas of various organs, [30][31][32] these coding RNAs probably are also involved in intensifying the malignant potential of vimentin-positive IBC-NSTs. In this study, although we also examined the tumor specimens for the 58 coding RNAs that have previously been reported as being significantly associated with EMT, only two were found to be significantly upregulated in vimentin-positive IBC-NSTs according to the FDR value (11 according to the p value).…”
Section: Mitotic Cytokinesismentioning
confidence: 99%